Everyman's guide to bacterial insertion sequences - Siguier, Patricia; Gourbeyre, Edith; Varani, Alessandro [UNESP]; Ton-Hoang, Bao; Chandler, Michael (American Society for Microbiology, 2015)
We have divided this review into two major sections. In one, we have attempted to present an overview of our current understanding of prokaryotic insertion sequences (IS), their diversity in sequence, in organization and in mechanism, their distribution and impact on their host genome, and their relation to their eukaryotic cousins. We discuss several IS-related transposable elements (TE) which have been identified since the previous edition of Mobile DNA. These include IS that use single-strand DNA intermediates and their related domesticated relations, insertion sequences with a common region (ISCR), and integrative conjugative elements (ICE), which use IS-related transposases (Tpases) for excision and integration. Several more specialized chapters in this volume include additional detailed information concerning a number of these topics. One of the major conclusions from this section is that the frontiers between the different types of TE are becoming less clear as more are identified. In the second part, we have provided a detailed description of the expanding variety of IS, which we have divided into families for convenience. We emphasize that there is no quantitative measure of the weight of each of the criteria we use to define a family. Our perception of these families continues to evolve and families emerge regularly as more IS are added. This section is designed as an aid and a source of information for consultation by interested specialist readers.
Keywords: Bacterial insertion sequences; DDE transposases; DEDD transposases; Eukaryotic transposable elements; HUH transposases; Orphan insertion sequences; Prokaryotic relatives